Cognitive Impairment and Its Correlation with Depression - Khan, Sikandar Ali; Jalil, Jawad; Sajjad, Mehreen (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the correlation between the severity of depression and cognitive impairment. Study Design: Cross-sectional study. Place and Duration of Study: Department of Psychiatry, Combined Military Hospital, Gujranwala, Pakistan from May 2016 to December 2016. Methodology: The cross-sectional study was conducted on outpatients in the Department of Psychiatry at Combined Military Hospital Gujranwala. The diagnosis of depression was made based on the WHO’s ICD10 diagnostic criteria, and symptom severity was assessed using the Beck Depressive Inventory. Deirdre M. used the Montreal Cognitive Assessment version 7.1 to assess cognitive impairment. Results: Eighty-six subjects were included in this study. A comparison of cognitive impairment and depression revealed that in a total of 16 subjects with minimal depression, only 5 had cognitive impairment; in 14 subjects with mild depression, 11 showed cognitive impairment; 26 subjects had moderate depression, out of which 18 showed signs of cognitive impairment; and among 30 subjects with severe depression, there was cognitive impairment in 25 individuals. The Spearman correlation showed a weak correlation of 0.321 (p<0.001). Conclusion: A high level of depressive symptoms, although weak, is significantly correlated with cognitive impairment.